PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VB SDN 55 SEBANGAR - Silalahi, Zulkarnain; Hamizi, Hamizi; Erlisnawati, Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was backgrounded by the problem of low learning outcomes of social sciences of the fifth grade students SDN 55 Sebangar, with an average value of 63.1. Classically it was said to be unfinished because the Minimum Completeness Criteria or KKM specified was 70. One contributing factor was the teacher has not applied learning models in implementing learning activities. For that conducted a classroom action research as many as 2 cycles to students of class VB SDN 55 Sebangar totaling 26 students, consisted of 12 male students and 14 female students started from February to July 2015 which aimed to improve result social sciences students by implementing cooperative learning model. From the results of data analysis improving student learning outcomes, preliminary data showed that the average value of the class only 63.1 it meant students who completed only 11 (42.3%), meanwhile the students who did not completed total 15 persons (57.7%). After doing the action in the first cycle by implementing cooperative learning model, the value of average daily test on the first cycle to 74.0 it meant increased of 17.27%. Students who pass increased to 16 with the classical completeness reached 61.5%. In the daily test cycle II obtained the average value of the class of 79.8 by the number of students who completed 23 people and who did not completed just 3 people. It meant that the learning outcomes increased by 26.47% with the classical completeness reached 88.5%. Thus, it can be concluded that the implementation of cooperative learning model can improve social sciences learning outcomes of the fifth grade students SDN 55 Sebangar.Keywords: Cooperative Learning, Learning Outcomes of IPS